Kinetics of Irreversible Saponification Reactions in terms of changes in Reactant Concentration: Kinetika Reaksi Saponifikasi Irreversible ditinjau dari Perubahan Konsentrasi Reaktan - Lestari, Dwi Indah; Sari, Debi Anggun; Putri, Zeolita Prabu; Maranggi, Isma Uly (Jurnal Kimia dan Rekayasa, 2026)
This study aims to investigate the kinetics of the irreversible saponification reaction between triglycerides in cooking oil and sodium hydroxide (NaOH) by analyzing the changes in reactant concentrations over time. The reaction was carried out at 60 oC, and samples were collected every 5 minutes and analyzed by titration using 0.5 M HCl. The results showed that the concentration of NaOH decreased from 0.500 mol/L to 0.290 mol/L within 30 minutes, while triglycerides decreased from 0.203 mol/L to 0.133 mol/L. The kinetic data were evaluated using both second-order and pseudo first-order models to determine the most appropriate mechanism. The second-order model yielded an R2 value of 0.9069 with a rate constant of 0.0125 L-mol-1·min-1, whereas the pseudo first-order model exhibited better linearity with an R2 of 0.9296 and a rate constant of 0.0169 min-1. These results indicate that although the reaction is mechanistically bimolecular, the experimental conditions particularly the relative excess of NaOH caused the reaction to behave in accordance with pseudo first-order kinetics. Thus, the observed kinetic behavior is more accurately described by the pseudo first-order model, in which the decrease in triglyceride concentration plays a dominant role in controlling the reaction rate. This study provides further insight into the kinetic characteristics of saponification under laboratory operating conditions. AbstrakPenelitian ini bertujuan untuk mempelajari kinetika reaksi saponifikasi irreversible antara trigliserida dalam minyak goreng dan natrium hidroksida (NaOH) melalui analisis perubahan konsentrasi reaktan terhadap waktu. Reaksi dijalankan pada suhu 60 oC, dan sampel diambil setiap 5 menit untuk dianalisis melalui titrasi menggunakan HCl 0,5 M. Hasil pengamatan menunjukkan bahwa konsentrasi NaOH menurun dari 0,500 mol/L menjadi 0,290 mol/L dalam 30 menit, sedangkan trigliserida turun dari 0,203 mol/L menjadi 0,133 mol/L. Data kemudian dianalisis menggunakan model kinetika orde dua dan pseudo first-order untuk menentukan mekanisme reaksi yang paling sesuai. Model orde dua memberikan nilai R2 sebesar 0,9069 dengan konstanta laju 0,0125 L-mol-1·min-1, sedangkan model pseudo first-order menunjukkan linearitas lebih baik dengan R2 0,9296 dan konstanta laju 0,0169 min-1. Perbedaan ini menunjukkan bahwa meskipun reaksi secara mekanistik bersifat bimolekuler, kelebihan relatif NaOH menyebabkan reaksi tampak mengikuti pola pseudo first-order. Dengan demikian, kinetika teramati lebih akurat dijelaskan oleh model pseudo first-order, dimana penurunan konsentrasi trigliserida menjadi faktor pengendali utama laju reaksi. Hasil penelitian ini memperkuat pemahaman mengenai perilaku kinetika saponifikasi pada kondisi operasi laboratorium.